The Routledge Handbook of Translation and Culture - Carbonell i Cortés, Ovidi (Routledge handbooks in translation and interpreting studies, 2018)
The Routledge Handbook of Translation and Culture collects into a single volume thirty-two state-of-the-art chapters written by international specialists, overviewing the ways in which translation studies has both informed, and been informed by, interdisciplinary approaches to culture. The book's five sections provide a wealth of resources, covering both core issues and topics in the first part. The second part considers the relationship between translation and cultural narratives, drawing on both historical and religious case studies. The third part covers translation and social contexts, including the issues of cultural resistance, indigenous cultures and cultural representation. The fourth part addresses translation and cultural creativity, citing both popular fiction and graphic novels as examples. The final part covers translation and culture in professional settings, including cultures of science, legal settings and intercultural businesses.